2022
DOI: 10.14417/ap.1868
|View full text |Cite
|
Sign up to set email alerts
|

Medical rescuers’ occupational health during COVID-19: Contribution of coping and emotion regulation on burnout, trauma and post-traumatic growth

Abstract: The COVID-19 pandemic places unique challenges to medical rescuers’ occupational health. Thus, it is crucial to assess its direct and indirect impacts on key psychological outcomes and adaptation strategies. This study aims to analyse the impact of this pandemic on medical rescuers’ coping and emotion regulation strategies, and their levels of work-related psychological outcomes, such as burnout, trauma and post-traumatic growth. Additionally, it aims to analyse the contribution of coping and emotion regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thirteen studies were conducted on healthcare workers (86.6%) ( 39 , 41 51 , 53 ), one on frontline workers (6.7%) ( 52 ), and one on psychologists (6.7%) ( 40 ). Concerning sample size, one study (6.7%) had a sample ≤ 100 ( 51 ), six (40.0%) had a sample size between 101 and 200 ( 39 , 43 , 44 , 47 , 50 , 53 ), two (13.3%) had a sample size between 201 and 500 ( 40 , 49 ), two (13.3%) between 501 and 1,000 ( 45 , 46 ), and four (26.6%) had a sample size ≥ 1,000 ( 41 , 42 , 48 , 52 ). Most included studies ( n = 13, 86.6%) included a majority of female workers ( 39 49 , 51 , 52 ), and only two studies (13.3%) included a majority of male workers ( 50 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies were conducted on healthcare workers (86.6%) ( 39 , 41 51 , 53 ), one on frontline workers (6.7%) ( 52 ), and one on psychologists (6.7%) ( 40 ). Concerning sample size, one study (6.7%) had a sample ≤ 100 ( 51 ), six (40.0%) had a sample size between 101 and 200 ( 39 , 43 , 44 , 47 , 50 , 53 ), two (13.3%) had a sample size between 201 and 500 ( 40 , 49 ), two (13.3%) between 501 and 1,000 ( 45 , 46 ), and four (26.6%) had a sample size ≥ 1,000 ( 41 , 42 , 48 , 52 ). Most included studies ( n = 13, 86.6%) included a majority of female workers ( 39 49 , 51 , 52 ), and only two studies (13.3%) included a majority of male workers ( 50 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…AlJhani et al ( 49 ) found that active coping was predictive of burnout ( p < 0.01). Fonseca et al ( 50 ) reported that dysfunctional coping was predictive of burnout ( p < 0.001). Miller et al ( 53 ) highlighted behavioral disengagement as predictive of burnout ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations